Seaweed-derived bioactives: Gut microbiota targeted interventions for immune function - Holly Sedgwick; Glenn Gibson; Jessica Adams; Anisha Wijeyesekera (Journal of Functional Foods)
Foods resistant to upper gastrointestinal digestion may undergo fermentation by microbial populations within the large intestine, which can induce alterations in the microbial ecology and metabolites, and consequently have implications for host health. Synbiotics are dietary-driven approaches of targeting the microbiota to improve immune health. Here, we review the potential of seaweeds, and bacteria able to ferment them, to play a role in the development of next generation synbiotics. Brown seaweed bioactives, particularly polysaccharides, are fermented by the microbiota and may have prebiotic potential, although needs greater confirmation in vivo. Alginate, laminarin, and in some cases fucoidan, have shown to modify the microbiota, its metabolites, and immune system function in in vitro research. Selected species of Bacteroides ferment these polysaccharides and have been shown to exert immunomodulatory effects in animal models. Further research is now required in humans to determine whether combinations of these could offer synergistic benefits for health.